2004
DOI: 10.1152/ajpheart.00073.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reversible effects of isoproterenol-induced hypertrophy on in situ left ventricular function in rat hearts

Abstract: The aim of the present study was to evaluate specifically left ventricular (LV) function in rat hearts as they transition from the normal to hypertrophic state and back to normal. Either isoproterenol (1.2 and 2.4 mg.kg(-1).day(-1) for 3 days; Iso group) or vehicle (saline 24 microl.day(-1) for 3 days; Sa group) was infused by subcutaneous implantation of an osmotic minipump. After verifying the development of cardiac hypertrophy, we recorded continuous LV pressure-volume (P-V) loops of in situ ejecting hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 30 publications
7
39
0
5
Order By: Relevance
“…Cell size, measured with area of myocyte, was also significantly larger in HYP than the one of CONT. These data are substantially the same as those previously reported by us [10].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Cell size, measured with area of myocyte, was also significantly larger in HYP than the one of CONT. These data are substantially the same as those previously reported by us [10].…”
Section: Resultssupporting
confidence: 92%
“…Distinct collagen accumulation was confirmed in the HYP slices used in the present study, as shown by previous papers including ours [9,10]. Our data also indicated that collagen contents measured by hydroxyproline methods in HYP (1.69 ± 0.21% collagen/LV dry weight; n = 6) were significantly (P \ 0.05) larger than those in CONT (1.33 ± 0.23% collagen/LV dry weight; n = 5), though the difference was small.…”
Section: Collagen Accumulationsupporting
confidence: 92%
See 2 more Smart Citations
“…Accordingly, we have proposed that PVA at midrange LV volume (PVA mLVV ) is a good mechanoenergetic index to evaluate LV function in the in situ normal rat heart (1 -3). Furthermore, we have validated the accuracy of the measurement of LV volume (LVV) in the in situ hypertrophic rat heart with a conductance catheter method (4). Using this method, we found that the changes in PVA mLVV sensitively reflected the formation and reversibility of isoproterenolinduced cardiac hypertrophy mediated by β 1 -receptor stimulation (4).…”
Section: Introductionmentioning
confidence: 94%